Economic Competitiveness Development Challanges in Western Balkan Countries - ASLLANI, Gani; VULA, Veton (Journal of Advanced Research in Law and Economics, 2018)
This paper intends is to analyze and give a functioning overview of the national protection and competition development authorities in the Western Balkan countries. To explain how much  these authorities are in compliance with EU rules and activities, to detail the implementation level of competition rules in the former Yugoslav Republics, to provide an overview how far these countries are in fulfilling their obligation based on Stabilisation and Association Agreement. Also, this paper intends to find the formula to build a strong and efficient National Competition Authorities as a prerequisite to ensure the effective implementation of the law on protection of competition and market economy functioning. Finally, the paper shows the level of implementation of competition rules from these candidate countries for EU membership in accordance with EU directives dealing with prohibited agreements, abuse of dominant position, concentration and state aid. Finally, the paper shows the level of implementation of competition rules from these candidate countries for EU membership in accordance with EU directives dealing with banned agreements, abuse of dominant position and state aid.